Synthesis and evaluation of bis(imino)anthracene derivatives as G-quadruplex ligands. Issue 5 (26th March 2021) - Coban, Tomris; Robertson, Cameron; Schwikkard, Sianne; Singer, Richard; LeGresley, Adam
Abstract : The synthesis of a small number of bis(imino)anthracene derivatives is reported. They were evaluated via NMR for binding efficacy to the G-quadruplex-forming oligonucleotide sequence (TTGGGTT) and show activity against the HeLa cancer cell line. Abstract : The synthesis of a small number of bis(imino)anthracene derivatives is reported. They were evaluated via NMR for binding efficacy to the G-quadruplex-forming oligonucleotide sequence (TTGGGTT) and show activity against the HeLa cancer cell line. These novel ligands are compared to previously synthesised G-quadruplex ligands that target telomeres and oncogenes.